Common Chinese Materia Medica Volume 8 - Ye, Huagu; Li, Chuyuan; Ye, Wencai; Zeng, Feiyan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This eighth volume describes 272 species of 13 families of medicinal plants, which are commonly used in Chinese medicine. The most important species are Adenophora stricta, Adenophora tetraphylla, Codonopsis pilosula, Codonopsis tangshen and Platycodon grandiflorus of Campanulaceae; Lobelia chinensis of Lobeliaceae; Hyoscyamus niger, Lycium barbarum and Lycium ruthenicum of Solanaceae; Cuscuta australis, Cuscuta chinensis, Erycibe obtusifolia of Convolvulaceae; Lagotis brevituba, Rehmannia glutinosa, Scrophularia ningpoensis of Scrpophulariaceae; Aeginetia indica, Cistanche deserticola, Cistanche of Orobanchaceae; Campsis grandiflora, Oroxylum indicum of Bignoniaceae; Andrographis paniculata, Strobilanthes cusia of Acanthaceae; Callicarpa formosana, Callicarpa kwangtungensis, Clerodendrum cyrtophyllum, Clerodendrum fortunatum, Verbena officinalis, Vitex trifolia of Verbenaceae; Agastache rugosa, Ajuga decumbens, Clerodendranthus spicatus, Clinopodium chinense, Glechoma longituba, Lamiophlomis rotata, Leonurus japonicus, Lycopus lucidus var. Hirtus, Mesona chinensis, Perilla frutescens, Pogostemon cablin, Prunella vulgaris, Salvia bowleyana, Salvia miltiorrhiza, Schizonepeta tenuifolia, Scutellaria baicalensis of Lamiaceae. In each specie, it introduces the scientific names, medicinal names, morphologies, habitats, distributions, acquisition and processing methods of these medicinal plants, the content of medicinal properties, therapeutic effects, usage and dosage of these medicinal plants, and attaches unedited color pictures and pictures of part herbal medicines of each species. This book series has 10 volumes in total, which covers over 2000 kinds of Chinese medicines that are commonly used. These volumes not only introduce the efficacy function and some prescriptions of the medicines, but also introduce the biological characteristics of them in detail with clear photos of the habitats, so that readers can identify them in the field. Apart from the growing environment, the books expound the distribution areas and other information to facilitate researches and other applications. The volumes are targeted at readers of general interests and it is also of high referential value for scientific researcher and teachers. It can be used as a guide to researchers, clinical doctors, and students in the department of pharmaceutics and traditional Chinese medicine.
Adenophora stricta -- Adenophora tetraphylla -- Codonopsis pilosula -- Codonopsis tangshen and Platycodon grandiflorus of Campanulaceae; Lobelia chinensis of Lobeliaceae; Hyoscyamus niger -- Lycium barbarum and Lycium ruthenicum of Solanaceae; Cuscuta australis -- Cuscuta chinensis -- Erycibe obtusifolia of Convolvulaceae; Lagotis brevituba -- Rehmannia glutinosa -- Scrophularia ningpoensis of Scrpophulariaceae; Aeginetia indica -- Cistanche deserticola -- Cistanche of Orobanchaceae; Campsis grandiflora -- Oroxylum indicum of Bignoniaceae; Andrographis paniculata -- Strobilanthes cusia of Acanthaceae; Callicarpa formosana -- Callicarpa kwangtungensis -- Clerodendrum cyrtophyllum -- Clerodendrum fortunatum -- Verbena officinalis -- Vitex trifolia of Verbenaceae; Agastache rugosa -- Ajuga decumbens -- Clerodendranthus spicatus -- Clinopodium chinense -- Glechoma longituba -- Lamiophlomis rotata -- Leonurus japonicus -- Lycopus lucidus var. Hirtus -- Mesona chinensis -- Perilla frutescens -- Pogostemon cablin -- Prunella vulgaris -- Salvia bowleyana -- Salvia miltiorrhiza -- Schizonepeta tenuifolia -- Scutellaria baicalensis of Lamiaceae.
Keywords: Pharmacy; Medicine; Plants$1 (BEvolution.s; Pharmacy; Clinical Medicine; Plant Evolution; Materia Medica